Smaller Orders of Insects of the Galápagos Islands, Ecuador : Evolution, Ecology, and Diversity. - Peck, Stuart B. (NRC Research Press, 2001)
The Galápagos Islands of Ecuador are world famous for their unique plants and animals, and the hints these gave to Charles Darwin in forming his ideas on evolution. They are the world's least altered set of tropical oceanic islands. The oldest have been available for colonization by land plants and animals for about 3-4 million years.